Influence of component damage on the mechanical performance of bracket set joints in ancient timber structures. Issue 8 (11th June 2022) - Dai, Lu; Chen, Jiuzhang; Chen, Xueyao; Ren, Haobo
Abstract: Ancient Chinese heritage buildings have high historical and artistic value. The bracket set in heritage buildings plays an important role in transferring and bearing load. However, over time, damage appears in these heritage buildings, which is especially serious in bracket sets. As damage seriously affects the safety and stability of the structure, studying the mechanical properties of the damaged bracket set and analyzing its influence on the entire structural system is vital for protecting ancient timber structures. This paper studies the influence of two kinds of damage on the mechanical properties of the bracket set. The model experiment results show that the force area reduction of the components in bracket sets has a distinct influence on the bearing and deformation capacities of the bracket set, with the impact on the stiffness of the bracket set being most significant. When damage occurs in the first layer of the Gong, the effect on the strength and the stiffness of the bracket set is the greatest. Numerical simulation shows that although the lateral displacement of the component will affect the seismic performance of the bracket set, the energy consumption ability remains good. The sidesway of the Cap Block has the greatest influence on the seismic behavior of the bracket set.